The possibility of winning in casino table games using probability theory and game theory. - Chia, Derrine Mei Mei. (2009)
This final year project serves as a resource for those with a desire to learn more about certain casino table games and also provide the information necessary to develop the understanding of gaming operations. The objective of this project is to look for loopholes in certain casino table games so as to reduce the house edge of the various games to the lowest. In this final year project, only four table games Pontoon, Roulette, Tai Sai and Three Card Poker are analyzed by us. Topics discussed within this project involve a comprehensive description of how casino table games are played, methodology and mathematics of the various games. In addition, we have also included an analysis of our empirical findings and limitations of the study.